2020
DOI: 10.1088/2053-1591/ab8b86
|View full text |Cite
|
Sign up to set email alerts
|

A new two-step selective laser remelting of 316L stainless steel: process, density, surface roughness, mechanical properties, microstructure

Abstract: A new two-step selective laser remelting (SLR) process was proposed to fabricate 316L stainless steel. The density, surface roughness, and mechanical properties were investigated by a multifunctional density tester, surface roughness meter, and tensile testing machine. Compared with the single-melting selective laser melting (SLM) process, the relative density, surface roughness (R a ), ultimate tensile strength, yield strength, elastic modulus, and elongation reached 99.31%, 6.67 μm, 725 MPa, 643 MPa, 13.95 G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In this study, printability refers to successfully building apart, and concurrently avoiding or minimizing macrocracking defects and delamination. Lu et al (2020) and Zhang et al (2019) have reported that in their studies, when remelting was done at a different angle than the first scanning, with NiTi elementally blended powders, when changing the direction of remelting, the laser collects welding contaminations on the part surface. That collection of contaminations causes surface roughness and porosity.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, printability refers to successfully building apart, and concurrently avoiding or minimizing macrocracking defects and delamination. Lu et al (2020) and Zhang et al (2019) have reported that in their studies, when remelting was done at a different angle than the first scanning, with NiTi elementally blended powders, when changing the direction of remelting, the laser collects welding contaminations on the part surface. That collection of contaminations causes surface roughness and porosity.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it was interesting to find that that the temperature increased again in Point D. This is mainly due to the influence of heat transfer on the first-pass molten pool during the second-pass melting molten pool, and the maximum temperature increases to 1200℃(less than 1357.77℃), which avoids the remelting of the firstpass molten track and the grain growth [19][20][21]. Therefore, laser process parameters (hatching space 0.08 mm) meet the requirements of overlapping rate and non-remelting.…”
Section: Temperature Flowmentioning
confidence: 99%
“…The relationship between volumetric energy density and defects (pores, bubbles and cracks, etc) of 316L stainless steel has been systematically studied by authors in [9,10]: Too low or too high volumetric energy density will lead to balling. Low volumetric energy density leads to incomplete melting or even no-melting of metal powder, resulting in pores; excessive volumetric energy density resulted in liquid metal splashing, bubbles and even cracks.…”
Section: Mesoscopic Numerical Model For L-pbf Processmentioning
confidence: 99%